Structural modeling of antibody variable regions using deep learning—progress and perspectives on drug discovery - Jaszczyszyn, Igor; Bielska, Weronika; Gawlowski, Tomasz; Dudzic, Pawel; Satława, Tadeusz; Kończak, Jarosław; Wilman, Wiktoria; Janusz, Bartosz; Wróbel, Sonia; Chomicz, Dawid; Galson, Jacob D.; Leem, Jinwoo; et al. (Frontiers in Molecular Biosciences, 2023)
AlphaFold2 has hallmarked a generational improvement in protein structure prediction. In particular, advances in antibody structure prediction have provided a highly translatable impact on drug discovery. Though AlphaFold2 laid the groundwork for all proteins, antibody-specific applications require adjustments tailored to these molecules, which has resulted in a handful of deep learning antibody structure predictors. Herein, we review the recent advances in antibody structure prediction and relate them to their role in advancing biologics discovery.